Integrating Diverse Study Abroad Opportunities Into Public Health Curricula: Three Distinct Strategies to Address Common Barriers - Laura Rusnak; J. Tory Peek; Deidre Orriola; Matawal Benjamin Makut (Frontiers Media S.A., 2019)
Background: To effectively train future leaders, undergraduate public health programs must prepare students to address challenges with cross-cultural competence and a global perspective. Study abroad programming represents a high impact practice that can be applied to any number of areas and topics within the field of public health. Infusing global learning into undergraduate curriculum, increases confidence in serving culturally diverse populations and aligns with multiple public health accreditation standards. Unfortunately, barriers often prevent integration of this high impact practice into program curriculum. This manuscript provides strategies to integrate diverse study abroad programming into public health curriculum and mitigate common barriers for students and faculty.Methods: Faculty from the University of South Florida (USF) College of Public Health (COPH) used three strategies to improve access to global learning: Adding public health courses to established study abroad programsUtilizing academic travel companiesLeveraging existing international and university partnerships.Results: A diverse array of public health-focused study abroad programs resulted from these strategies. Starting with just 12 students in the first program, the number of undergraduate participants in short-term, faculty lead courses grew to 164 students over the span of 4 academic years. This represents a 275% increase in undergraduate students participating in public health-focused study abroad courses, and a 160% increase in the percentage of public health majors participating in study abroad coursework. The primary barriers of cost, curriculum, and academic culture were addressed throughout development of each new program.Conclusions: Infusing study abroad programs into the public health curriculum provides students with diverse opportunities to gain the skills they will need as public health practitioners. The design and implementation of the strategies that were used to successfully integrate global learning into one public health program's curriculum can help inform other schools and programs of public health on ways to increase student utilization of this high-impact practice.